CHERRY PICK, SHOPPING SATISFACTION, AND MARKET MAVEN - Endang Ruswanti (Journal of Economics, Business, and Accountancy Ventura, 2013)
The study examines the effect of five dimensions of selective consumers, commonly known as cherrypick, on market maven mediated by shopping satisfaction. For practitioners, cherry pickers havecontributed to a lot in building price competition among retailers, or retailers trying to have thecheapest deals in the weekly ad and the discount price. Cherry pickers are interested in shoppingwith the discount price of 50% -70%. As retail management strategy, it has the aim to gain biggerturnover. The segment of cherry pick has been discovered quite large, heterogeneous, and potentiallyattractive to retail management. Market maven functions as non-cost promotional tool byvoluntarily conveying to consumers who need information about product, brand, price, deficiencyand excess product, place of purchase and method of payment. It shows that the dimensions of attractivediscount 50%-70% and the consideration for the purchase of discount product affect shoppingsatisfaction. Shopping satisfaction affects the market maven. Dimensions of discount 50%-70% and discount information affect the market maven. Consumers who have market maven natureneed to know the description on large discount retail offer and discount information so that theycan be conveyed voluntarily to consumers in need. Women tend to be more cherry picking andmarket maven than men at the age of 31-50 years.